Hubungan Stres Akademik dengan Gangguan Siklus Menstruasi pada Siswi Sekolah Menengah Atas: Studi Cross-Sectional di SMA Nurcahaya Medan - Nisrina; Purwaningsih (Lembaga Intelektual Muda (LIM) Maluku, 2026)
Menstrual cycle disorders remain a reproductive health problem in adolescent girls, and prolonged academic stress can disrupt hormonal regulation through dysfunction of the hypothalamic-pituitary-adrenal and hypothalamic-pituitary-ovarian axes, thus triggering menstrual cycle irregularities. This study aims to analyze the relationship between academic stress and menstrual cycle disorders in female students at Nurcahaya High School, Medan. The study used a quantitative, correlational analytical design with a cross-sectional approach, conducted in July 2026 on 40 female students selected through purposive sampling. Academic stress was measured using the Educational Stress Scale for Adolescents (ESSA) and menstrual cycle disorders using a validated menstrual cycle questionnaire. Data were analyzed univariately and bivariately using the Chi-Square test at a significance level of p < 0.05. The results showed that 45.0% of respondents experienced moderate academic stress and 30.0% experienced severe academic stress, while 60.0% experienced menstrual cycle disorders. A chi-square test showed a significant association between academic stress and menstrual cycle disorders (p = 0.014). This finding confirms that academic stress is an important psychobiological determinant of menstrual irregularities in adolescents and emphasizes the need for school-based reproductive health nursing interventions.